LITERASI DIGITAL DALAM PERSPEKTIF GURU DI WILAYAH PEDESAAN PULAU TIMOR - FEMBERIANUS SUNARIO TANGGUR (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2022)
The purpose of this research is to find out the teacher's perspective on digital literacy in the rural areas of Timor Island. The research approach is qualitative with descriptive method. Research informants are school principals, teachers and students. Data collection techniques using observation, interviews, document studies, questionnaires. Data Analysis Techniques consist of 3 streams of activities that are carried out simultaneously, namely data reduction, data presentation and conclusion/verification. The results of the study are that the diverse perspectives of teachers regarding digital literacy in schools have a low impact on the implementation of digital literacy at SDN Balfai, Kupang Regency. Out of a total of 29 teachers, there were 23 (79%) teachers who had not participated in digital literacy training activities, 6 teachers who had participated in digital literacy training activities (21%) The difference in perspective was the result of various problems in implementing digital literacy in schools, namely: First, the low level of teacher understanding of digital literacy is influenced by the lack of digital literacy training for teachers. Second, apart from that, the weak managerial role of school principals in formulating work programs to implement digital literacy in schools results in the absence of digital literacy programs. Third, the low role of the teacher in implementing school digital literacy. Fourth, online learning activities carried out during the Covid -19 pandemic have not had an impact on digital literacy habits for teachers and students.